CARDIAC RUPTURE IN MYOCARDIAL INFARCTION: INCIDENCE AND PREDISPOSING FACTORS (15 YEAR FOLLOW-UP) - V. A. Shulman; S. E. Golovenkin; V. V. Radionov; T. M. Parfenova; G. V. Matyushin (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the incidence of cardiac rupture (CR) in patients with acute myocardial infarction (MI) as well as predisposing factors during 15-year follow-up.Material and methods. 1453 patients with acute MI who were admitted to Krasnoyarsk cardiological center during 1989, 1993 and 2003 years were studied. All patients were divided into three groups: group I - 447 patients, who were on treatment in 1989, group II - 475 patients of 1993, and group III – 531 patients of 2003. There were no differences in groups on patient sex, location and depth of MI, previous MI, arrhythmias, heart failure and diabetes mellitus.Results. CR was found in 18 of 447 patients (4%) of group I (1989), in 16 of 475 patients (3,4%) of group II (1993) and in 10 of 531 patients (1,9%) of group 3 (2003), (p1,3 <0,05). Incidence of CR significantly decreased from 1989 to 2003 in female patients (7,2%; 5,7% and 1,6% in 1989, 1993 and 2003, respectively; p1,3 < 0,01, p2,3 < 0,05). Incidence of CR in male patients didn’t changed (2,5%, 1,8% and 2,1%, respectively). The average blood pressure (BP) during the first day of MI in female patients was higher than this in male ones in 1989 and 1993. There were no significant differences in BP between women and men in 2003. Heart rate (HR) during the first day of MI in female patients was higher than this in male patients in 1989. However in 1993 and 2003 there were no differences in HR between women and men. MI therapy more often included betablockers, angiotensin converting enzyme inhibitors, intravenous nitrates, statins, thrombolythics and anticoagulants in 2003 than in 1989 and 1993.Conclusion. Effective BP and HR control is the most effective way to prevent CR in patients with MI.